Hydrological and hydrochemical regime of the main rivers of the Kabardino-Balkar high-mountain state reserve under conditions of modern climate change - I. I. Kuchmenova (Наука. Инновации. Технологии)
In recent decades, there has been an increase in water resources and a change in the intra-annual distribution of runoff in many areas of the European part of Russia. Rising air temperatures lead to increased glacier melting, but these issues have been considered mainly for large rivers; small mountain rivers have been little studied. This article discusses the impact of changes in meteorological characteristics (air temperature and precipitation) on the hydrological and hydrochemical regime of the rivers of the Kabardino-Balkar State High-Mountain Reserve. Climate changes are analyzed based on air temperature and precipitation data for the period from 1961 to 2021. The water regime is analyzed based on long-term runoff data from the villages of N. Chegem and Babugent over the period from 1961 to 2021. A comparative analysis of data on the sum of ions in the water of the studied rivers for 1958– 1960 was carried out with the data we obtained in 2015–2017. Long-term fluctuations in air temperature for all studied basins tend to increase: average annual and winter by 0.6 ºС, summer from 2.4 to 3 ºС. An increase in the annual precipitation amount is typical for the village of N. Chegem by more than 5 mm, the amount of precipitation in summer increases by almost 10 mm, while in winter there is a decrease of 5 mm over the period under review. An all-season decrease in precipitation is typical for the village of Babugent: the annual precipitation amount decreases by 84 mm, summer by 78 mm, winter by 5 mm. A comparative analysis of the data the author obtained for 2015–2017 with the mineralization of rivers for 1958-1960 revealed that by now the mineralization of rivers in low water has decreased by almost 5 times; in flood — more than 2 times.